2011
DOI: 10.1002/humu.21526
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 genotype, athletic status, and life course physical capability: meta‐analysis of the published literature and findings from nine studies

Abstract: The ACTN3 R577X (rs1815739) genotype has been associated with athletic status and muscle phenotypes, although not consistently. Our objective was to conduct a meta-analysis of the published literature on athletic status and investigate its associations with physical capability in several new population-based studies. Relevant data were extracted from studies in the literature, comparing genotype frequencies between controls and sprint/power and endurance athletes. For life course physical capability, data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
2
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 74 publications
6
78
2
8
Order By: Relevance
“…15 The 577RR genotype has been previously associated with elite, power-oriented athletic status (i.e., sprinters, jumpers and throwers) in several cohorts of Caucasian athletes, 5,6,19 with one exception. 20 With regards to this, a recent meta-analysis showed a strong association between the 577RR genotype and power athletic performance especially among Europeans, regardless of the significant heterogeneity among the groups of athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The 577RR genotype has been previously associated with elite, power-oriented athletic status (i.e., sprinters, jumpers and throwers) in several cohorts of Caucasian athletes, 5,6,19 with one exception. 20 With regards to this, a recent meta-analysis showed a strong association between the 577RR genotype and power athletic performance especially among Europeans, regardless of the significant heterogeneity among the groups of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…20 With regards to this, a recent meta-analysis showed a strong association between the 577RR genotype and power athletic performance especially among Europeans, regardless of the significant heterogeneity among the groups of athletes. 15 Team sports are intermittent in nature and require the repetition of powerful movements including short-distance sprinting and jumping, 21 and these actions require the working muscles to produce force at a high velocity. 22 We therefore hypothesised that the 577RR genotype frequency distribution would be higher in team-sport athletes compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of several meta-analyses have allowed establishing that the total number identified to date, genetic markers, only 31 showed positive associations with athlete status in at least 2 studies and 12 in 3 or more studies [27,28,34,40]. On the other hand, the value of the 29 markers (24%) had played in at least one study that indicates a possible false-positivity of information.…”
Section: -mentioning
confidence: 99%
“…In a meta-analysis Alfred, et al [27] it is shown that the ACTN3 RR genotype is more common among European athletes speed and power sports than among athletes. In another metaanalysis Ma, et al [28] also found a positive Association between the ACTN3 RR and RX genotypes and athletic status in speed-power kinds of sports, but only in European populations, but not in Asian or African.…”
mentioning
confidence: 99%